The Relationship Between Organizational Agility and Strategic Entrepreneurship: An analytical Research in Some Companies at the Ministry of Agriculture in Iraq - Ameen Salim Alborathy, Ahmed; Masmoudi, Faouzi; Mohammed Ismael , Firas (Journal of Economics and Administrative Sciences, 2024)
The research aims to test the correlation between organizational agility (AO) as an independent variable and strategic entrepreneurship as a dependent variable in the firms belonging to the Ministry of Agriculture of Iraq. Interest in these variables has increased as they contribute to environmental adaptation to maintain corporate value and reduce competition. To analyze the correlation between the study’s variables, a set of objectives was formulated to reveal the nature of the correlation between organizational agility and strategic entrepreneurship, if any, in selected companies. Hypotheses were formulated to be notably related to the relationship association and influence organizational agility and its dimensions in strategic entrepreneurship. The study community reached 102 individuals. Because the study sample was (stratified) within the same level as the managers, 93 out of 102 individuals, questionnaires were retrieved. The SPSS program was used by utilizing appropriate statistical methods. The results demonstrated the acceptance of correlation and impact on the level of macro and sub-variables, and the study concluded that organizational agility behaviors need to be adopted by the organization due to an immediate response to understanding changes in the environment in terms of exploring opportunities and making flexible decisions towards investing in advantages towards strategic entrepreneurship. Paper type: Analytical study in companies of the Ministry of Agriculture.